Reverse planning for making an occlusal splint before restorative treatment: case report of rehabilitation of a patient with bruxism (Research, Society and Development, 2020)
Recovery of worn tooth surfaces using composite resin has been increasingly accepted by clinicians, since rehabilitation through additive techniques aims at minimal or no intervention and preserves healthy dental structure, ensuring longevity to the treatment. Adhesive dentistry can afford promising results through a correct diagnosis and treatment plan. Planning can offer not only dental rehabilitation, but also controlling cause of the wear process. Strategies that seek to prevent the progression of muscle activities such as bruxism, should be established. This article aims to present a clinical case report of a rehabilitation treatment planned and executed through the digital flow, in which the patient presents wear and tear caused by the habit of bruxism. The rehabilitation of the anterior upper teeth was carried out in direct composite resin, associated with the preparation and installation of an occlusal splint, used before, during and after the restorative treatment, ensuring the reestablishment of the shape, function and dental aesthetics.